Internet regulation as media policy: Rethinking the question of digital communication platform governance. (1st March 2019) - Flew, Terry; Martin, Fiona; Suzor, Nicolas
This article identifies the current global 'techlash' towards the major digital and social media platforms as providing the context for a renewed debate about whether these digital platform companies are effectively media companies (publishers and broadcasters of media content), and implications this has for twenty-first-century media policy. It identifies content moderation as a critical site around which such debates are being played out, and considers the challenges arising as national and regionally based regulatory options are considered for digital platforms that are 'born global'. It considers the shifting balance between the 'social contract' of public interest obligations and democratic rights of free speech and freedom of expression.